The content and construct development of the PACT survey. (June 2019) - Miller, Rachelle; Wake, Donna; Whittingham, Jeff; Adelson, Jill L.
Highlights: Teacher survey created to evaluate perceptions of arts integration. Exploratory and confirmatory factor analyses completed. Appropriate factor loadings and high reliability coefficients across all constructs. Abstract: The authors created a psychometrically sound instrument that could be used to examine K-12 teachers' perceptions of arts integration. Ten content experts reviewed the initial survey items for construct-fit and readability. Scores from 354 K-12 teachers were examined for the survey's initial factor structure through exploratory factor analysis (EFA). Then, scores from 1, 072 K-12 teachers were analyzed to complete a confirmatory factor analysis (CFA) of the Putting the Arts and the Classroom Together (PACT) data. EFA results indicated a three-factor structure (i.e., value, willingness, and barriers), and CFA results produced model indices showing good fit of the three-factor model. For purposes of examining teachers' practices in integrating the arts, establishing teacher receptiveness to arts integrated curriculum is important in designing and implementing any professional development program. This survey could be used to establish baseline participant perceptions for staging targeted professional development to support educators in creating appropriate arts integrated curricula.